1998
DOI: 10.1177/105477389800700105
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment of Males on Three Types of Dialysis

Abstract: End-stage renal disease (ESRD) is a chronic illness that challenges the coping ability of patients and their families, demanding behavioral and emotional lifestyle changes. The purposes of this comparative descriptive study were to explore the anxiety, depression, and psychosocial adjustment of male patients on three types of dialysis--home hemodialysis (home HD), in-center hemodialysis (in-center HD), and peritoneal dialysis (PD)--and to identify perception of hemodialysis stressors for those on home HD and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Comparison of the anxiety and depression score of the patients on home HD with the scores of patients on in-center HD and PD indicate that patients on home HD had lower anxiety and depression scores (Courts & Boyette, 1998). Dialysis partners also had low anxiety and depression scores, supporting other findings that home HD stress for partners decreases over time (Lowry & Atcherson, 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Comparison of the anxiety and depression score of the patients on home HD with the scores of patients on in-center HD and PD indicate that patients on home HD had lower anxiety and depression scores (Courts & Boyette, 1998). Dialysis partners also had low anxiety and depression scores, supporting other findings that home HD stress for partners decreases over time (Lowry & Atcherson, 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Among the 12 articles presented, eight were written by nurses and the others by physicians (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Resultsmentioning
confidence: 99%
“…Kane (1985) even suggests that contentment should be considered an ideal outcome for elderly people. Kane's view is supported by many authors who have used level of contentment as a variable to assess positive affect in nursing home residents with Alzheimer's disease (Lawton, VanHaitsma, & Klapper, 1996), as a variable to address when assessing marital relationships (Moroi, 1990), and as a measure of depression (see, for example, Attala, Oetker, & McSweeney, 1995;Courts & Boyette, 1998;Demers & Lavoie, 1996). Kane's view is supported by many authors who have used level of contentment as a variable to assess positive affect in nursing home residents with Alzheimer's disease (Lawton, VanHaitsma, & Klapper, 1996), as a variable to address when assessing marital relationships (Moroi, 1990), and as a measure of depression (see, for example, Attala, Oetker, & McSweeney, 1995;Courts & Boyette, 1998;Demers & Lavoie, 1996).…”
Section: Contentment Is a Human Experiencementioning
confidence: 99%
“…Only 11 studies were found in which the phenomenon of concern was contentment (Attala et al, 1995;Bylsma & Major, 1994;Courts & Boyette, 1998;Demers & Lavoie, 1996;Hirsch & Hirsch, 1995;Karaku, 1995;Kovacs, 1996;Kriedler, Campbell, Lanik, Gray, & Conrad, 1994;Lindgren, Svardsudd, & Tibblin, 1994;Lloyd-Cobb & Dixon, 1995;Pardeck & Chung, 1995). The findings of these various studies suggest that people's contentment with their health is related to life situation (Bylsma & Major, 1994;Lindgren et al, 1994), ability to live independently (Kriedler et al, 1994;Nilsson et al, 1996;Schmotkin & Hadari, 1996), and level of depression (Attala et al, 1995;Courts & Boyette, 1998;Demers & Lavoie, 1996;Hirsch & Hirsch, 1995;Kovacs, 1996;Lloyd-Cobb & Dixon, 1995;Pardeck & Chung, 1995).…”
Section: Contentment Is a Human Experiencementioning
confidence: 99%
See 1 more Smart Citation